Localization of an Aldo-Keto Reductase (AKR2E4) in the Silkworm Bombyx mori (Lepidoptera: Bombycidae) - Yamamoto, K (J Insect Sci, 2017)
The aldo-keto reductase AKR2E4 reduces 3-dehydroecdysone to ecdysone in the silkworm Bombyx mori L. In this study, a quantitative polymerase chain reaction analysis revealed that the level of AKR2E4 mRNA was higher in the testes than in other tissues, and a western immunoblot analysis revealed that the AKR2E4 content in the testes was stage-specific from the fifth larval instar to the pupal stage. Immunohistochemical analysis showed that the AKR2E4 protein was present in cyst cells associated with sperm cells and spermatocytes. These results indicate that AKR2E4 plays an important role in 3-dehydroecdysone conversion to ecdysone and spermatogenesis in silkworm testes.